Clinical Applications of Circulating Tumour Cells and Circulating Tumour DNA in Non-Small Cell Lung Cancer—An Update - Kapeleris, Joanna; Ebrahimi Warkiani, Majid; Kulasinghe, Arutha; Vela, Ian; Kenny, Liz; Ladwa, Rahul; O’Byrne, Kenneth; Punyadeera, Chamindie (Frontiers in Oncology, 2022)
Despite efforts to improve earlier diagnosis of non-small cell lung cancer (NSCLC), most patients present with advanced stage disease, which is often associated with poor survival outcomes with only 15% surviving for 5 years from their diagnosis. Tumour tissue biopsy is the current mainstream for cancer diagnosis and prognosis in many parts of the world. However, due to tumour heterogeneity and accessibility issues, liquid biopsy is emerging as a game-changer for both cancer diagnosis and prognosis. Liquid biopsy is the analysis of tumour derived biomarkers in body fluids, which has remarkable advantages over the use of traditional tumour biopsy. Circulating tumour cells (CTCs) and circulating tumour DNA (ctDNA) are two main derivatives of liquid biopsy. CTC enumeration and molecular analysis enables monitoring of cancer progression, recurrence, and treatment response earlier than traditional biopsy through a minimally invasive liquid biopsy approach. CTC derived ex-vivo cultures is essential to understanding CTC biology and their role in metastasis, provides a means for personalised drug testing and guides treatment selection. Just like CTCs, ctDNA provides opportunity for screening, monitoring, treatment evaluation, and disease surveillance. We present an updated review highlighting the prognostic and therapeutic significance of CTCs and ctDNA in NSCLC.